Determination of complete mitochondrial genome sequence from the holotype of the southern Mandarin dogfish Cirrhigaleus australis (Elasmobranchii: Squalidae). (2nd January 2016) - Yang, Lei; Matthes-Rosana, Kerri A.; Naylor, Gavin J. P.
Abstract: We determined the complete mitochondrial genome sequence from the holotype of the southern Mandarin dogfish Cirrhigaleus australis . It has a length of 16, 543 bp and consists of 13 protein-coding genes, 22 tRNA genes, 2 rRNA genes, and 1 control region. The gene composition and genome organization is similar to most other vertebrates. Data obtained in this study will be important for resolving possible taxonomic issues related to C. australis and will contribute to the reconstruction of phylogenetic relationships among chondrichthyan species.